2014
DOI: 10.1039/c4ra04836a
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-catalyzed synthesis of aniline oligomers and their application for the protection of copper against corrosion

Abstract: A new method for the enzymatic synthesis of oligoaniline soluble in organic solutions is developed. Aniline oligomers showed a high inhibition of copper corrosion in aqueous HCl and NaCl solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Kinetic studies of PANI synthesis catalyzed by soybean peroxidase (SBP) in water or water/organic solvent mixtures indicated that the enzymatic polymerization of aniline does not have an induction period or autoacceleration, which is characteristic for the simple chemical polymerization of aniline (Cruz-Silva et al 2005). Similarly, Shumakovich et al (2014) pointed out that the growth of PANI chain during the chemical oxidative polymerization of aniline occurs via the formation of oligomeric/polymeric pernigraniline intermediates which are later reduced by unreacted aniline molecules to the PANI emeraldine salt in the final polymerization phase. In contrast, oligoaniline and PANI chains in the emeraldine oxidation state are immediately formed in the laccase-catalyzed polymerization of aniline (Junker et al 2014a), i.e., the enzymatic polymerization of aniline proceeds without an induction period (initial accumulation of oligomeric pernigraniline intermediates).
Fig.
…”
Section: Enzymatic Oligomerization and Polymerization Mechanismsmentioning
confidence: 98%
“…Kinetic studies of PANI synthesis catalyzed by soybean peroxidase (SBP) in water or water/organic solvent mixtures indicated that the enzymatic polymerization of aniline does not have an induction period or autoacceleration, which is characteristic for the simple chemical polymerization of aniline (Cruz-Silva et al 2005). Similarly, Shumakovich et al (2014) pointed out that the growth of PANI chain during the chemical oxidative polymerization of aniline occurs via the formation of oligomeric/polymeric pernigraniline intermediates which are later reduced by unreacted aniline molecules to the PANI emeraldine salt in the final polymerization phase. In contrast, oligoaniline and PANI chains in the emeraldine oxidation state are immediately formed in the laccase-catalyzed polymerization of aniline (Junker et al 2014a), i.e., the enzymatic polymerization of aniline proceeds without an induction period (initial accumulation of oligomeric pernigraniline intermediates).
Fig.
…”
Section: Enzymatic Oligomerization and Polymerization Mechanismsmentioning
confidence: 98%
“…The MALDI spectrum is very crowded and each oligomer showed the presence of different peak clusters corresponding to its various redox states and different end groups . As an example, a mass increment of about 15 Da corresponding to polymeric species with loss of ‐NH 2 , may be the result of fragmentation of the sample in the desorption/ionization process, as reported elsewhere .…”
Section: Resultsmentioning
confidence: 53%
“…The MALDI spectrum is very crowded and each oligomer showed the presence of different peak clusters corresponding to its various redox states and different end groups [41]. As an example, a mass increment of about 15 Da corresponding to polymeric species with loss of -NH 2 , may be the result of fragmentation of the sample in the desorption/ionization process, as reported elsewhere [42][43][44][45]. As for pDANI, the spectra showed the presence of polymeric species in the range from 700 to 1600 Da, with peaks belonging to two families with different abundance (Supporting Information Figure 1B).…”
Section: Maldi Analysismentioning
confidence: 65%
“…Compared to peroxidases, the peroxide free action of laccases represents a significant advantage. However, the random character of radical reactions typically resulted in complex mixtures of oligomers and polymers . Another expected disadvantage was the possible requirement of a mediator for achieving reasonable yields .…”
Section: Enzyme Catalyzed Routes To Divanillinmentioning
confidence: 99%